Effects of Carbon Chain Length on N-Alkane Counterflow Cool Flames: A Kinetic Analysis - Dan Tian; Lei Xu; Dong Liu (Fire, 2022)
An in-depth understanding of the low-temperature reactivity of hydrocarbon fuels is of practical relevance to developing advanced low-temperature combustion techniques. The present study aims to study the low-temperature chemistry of several large n-alkanes with different carbon chain lengths in counterflow cool diffusion flames by kinetic analysis. The large n-alkanes that were chosen are n-heptane (NC7H16), n-decane (NC10H22) and n-dodecane (NC12H26), which are important components of practical fuels. Firstly, the thermochemical structure of a typical cool diffusion flame is understood through its comparison with that of a hot diffusion flame. The boundary conditions, including the ozone concentration, fuel concentration and flow velocity—where cool flames can be established—are identified with a detailed chemical mechanism that evaluates the low-temperature reactivity of the investigated n-alkanes. The results show that the n-alkane with a longer carbon chain length is more reactive than the smaller one, thereby indicating the order of NC12H26 > NC10H22 > NC7H16. This trend is qualitatively similar to the findings from non-flame reactors. The reaction pathway and sensitivity analysis are performed to understand the effects of carbon chain length on the low-temperature reactivity. The contribution of an n-alkane with a longer carbon chain to the dehydrogenation reaction, oxidation reaction and isomerization reaction is greater than that of a smaller n-alkane, and abundant O and OH radicals are generated to promote the fuel low-temperature oxidation process, thereby resulting in an enhanced low-temperature reactivity. The effects of ozone addition on the low-temperature reactivity of n-alkanes are also highlighted. It is found that the addition of ozone could provide a large number of active O radicals, which dehydrogenate with the fuels to generate OH radicals and then promote fuel low-temperature oxidation. The present results are expected to enrich the understanding of the low-temperature characteristics of large n-alkanes.